Telaah Epistemologi Positivisme dan Fenomenologi - Muhammad Sanusi (Asketik)
Epistemology is begun based on the need for philosophy used to recite social-cultural events. Nowadays, the development of epistemology is fast enough as proof of thinking way which is growing in academics and research, especially in social-cultural science. The growing epistemology is positivism, materialism, structuralism, hermeneutics, and phenomenology. Epistemology does not appear explicitly in research yet it is always there. Scientists and researchers should be aware of what epistemology is to use. It gives the benefit of the strength of the research. This article delivers about growing epistemology in social sciences. The two kinds of epistemology discussed in this article used a comparison approach; that is comparing both to find out the similarities and differences. Positivism is epistemology used in much social-cultural research while phenomenology responds to positivism and shows criticism of it.